Methylation of the 5' CpG islands and bladder cancer pathogenesis - (:unkn) unknown (My University, 1999)
Deregulation of cell cycle that results in uncontrolled cellular proliferation is the basis of neoplastic process. Bladder tumors are heterogenous in their behavior, and difficult to predict the clinical course order to alleviate this problem, been focused on mutations in various cell cycle regulators and their association with tumor behavior. Mutations of the p16/CDKN2 gene, encoding a cyclin dependent kinase inhibitor, are common in bladder cancer. In contrast to other tumor suppressor genes, the two most common mechanisms for loss of p16/CDKN2 function are homozygous deletion and loss of transcription associated with hypermethylation of the 5'CpG island region. Recently, it is found that methylation of p16/CDKN2 is potentially reversible with exposure to demethylating agents, such as 5-aza-2'-deoxycytidine, which is a well-established inhibitor of DNA methylation, which may open up new ways to effective tumor management.
Keywords: Bladder cancer; Cell cycle; Methylation